Predictors of length of stay in a psychiatric hospital. (2nd October 2015) - Gopalakrishna, Ganesh; Ithman, Muaid; Malwitz, Kari
Abstract : Objective . This article reviews the available evidence for predicting length of stay in a psychiatric hospital based on several patient characteristics. Methods. An OVID Medline search was done for studies in this area with terms: length of stay, acute psychiatric hospital and predictors. Indexed articles were searched for additional references and subsequently cross referenced. The variables described in various studies were classified into demographic, diagnostic, treatment related and system-based variables (Table 1 ). Results . Substance abuse has been consistently shown to be associated with a shorter length of stay. Mood and psychotic disorders have shown to lengthen the stay in an acute psychiatric hospital. Women tend to stay longer in an acute psychiatric hospital. Other demographic variables like age and education have had equivocal results, while a married marital status and employment are consistently related to a shorter length of stay. Use of restraints and ECT during hospitalization has shown to lengthen the stay in the hospital. Conclusions. Many studies have explored the relationship between the demographics, diagnosis and treatment variables on length of stay in an acute psychiatric hospital. These studies have been able to account for about 10–37% of the variance in the length of stay. The relevant findings impacting the length of stay are shown inTable 2 .